Original footage of the Chilean miners with manganism published in Neurology in 1967. (15th December 2015) - Miranda, Marcelo; Bustamante, M. Leonor; Mena, Francisco; Lees, Andrew
Abstract : Manganism has captured the imagination of neurologists for more than a century because of its similarities to Parkinson disease and its indirect but seminal role in the "L-dopa miracle." We present unpublished footage of the original case series reported in Neurology® in 1967 by Mena and Cotzias depicting the typical neurologic signs of manganism in 4 Chilean miners and their response to high doses of L-dopa.